After the El Dorado Decade: Spain's troubled path in managing its crisis - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2012)
Since the spring of 2012, the crisis in Europe has been shifting from the former epicenters of Greece, Portugal, and Ireland to Spain and Italy. In particular, the high level of unemployment in Spain has resulted in a choir of demands for increased public spending and a departure from austerity programs. The German government, and especially Chancellor Angela Merkel, is accused of being too stubborn in its demands for more fiscal prudence. American economist Paul Krugman, speculator-turned-philanthropist George Soros, and many others suggest that credit-financed spending would help Spain. In addition, dispatching aid to ailing Spanish banks is considered essential. However, the potential benefits of these policies are not convincing. Credit-financed stimulus programs would weaken the Spanish economy in the long run. On the other hand, large-scale rescue operations for Spanish banks would result in so much collateral damage that continuing on the current austerity path also appears unwise. But before the therapy, the patient's history ought to be examined: How did Spain - an economic poster child for over a decade - manage to slide into economic calamity?
Keywords: 320